Postoperative acute kidney injury and renal replacement therapy after DCD lung transplantation. Issue 2 (12th September 2021) - Verzelloni Sef, Alessandra; Sef, Davorin; Trkulja, Vladimir; Raj, Binu; Lees, Nicholas James; Walker, Christopher; McGovern, Ian; Mitchell, Jerry; De Robertis, Fabio; Stock, Ulrich
Abstract: Acute kidney injury (AKI) after lung transplantation (LTx) is a common complication. We aimed to assess whether donation after circulatory death (DCD) is associated with an increased risk of AKI and renal replacement therapy (RRT) in the early postoperative period compared to the donation after brain death (DBD). Retrospective data on a cohort ( N  = 95) of LTx patients (DCD n  = 17, DBD n  = 78) characterized by no use of ex‐vivo lung perfusion were analyzed for the incidence of AKI within 30 postoperative days and incidence of RRT within 7 and 30 days. After optimal full matching, an imbalance remained between the DCD and DBD patients in respect to intraoperative use of cardiopulmonary bypass (CPB). Therefore, a further subset ( n  = 77) was defined that excluded CPB patients, and matching was repeated (DCD n  = 13 vs. DBD n  = 63) resulting in a fair balance on a range of preoperative characteristics and intraoperative use of ECMO. In both matched subsets, DCD was associated with around twice higher risk of AKI and RRT within 7 and 30 postoperative days. In conclusion, data suggest that DCD could be associated with worse early renal outcomes in a subset of LTx patients and justify further studies on the topic in order to refine further renal care pathways perioperatively.